Clinical manifestations and prognosis of tuberculous spondylitis in an adolescent with disseminated tuberculosis: a case report - Handryastuti, Setyo; Kaswandani, Nastiti; Hendriarto, Andra; Tobing, Singkat Dohar Apul Lumban; -, Pebriansyah; Rafli, Achmad (Paediatrica Indonesiana, 2024)
Indonesia is one of the countries with the highest number of tuberculosis (TB) cases globally. Around 10-20% of adolescents with TB infection progress to pulmonary TB, and less than 0.5% develop miliary or central nervous system TB. TB spondylitis occurs in only 5.6% of extrapulmonary TB patients. The clinical manifestations of disseminated and TB spondylitis are heterogeneous and insidious, with several potential risk- and prognostic factors. We report the case of a 16-year-old male admitted with abdominal distension, paraplegia, and urinary retention. He was diagnosed with disseminated TB with TB spondylitis. This case was unique because the patient had no classic symptoms of pulmonary TB. This report focuses on the diagnosis, comprehensive management, and prognosis of TB spondylitis, as well as the risk factors for disseminated TB. The management consisted of antituberculous agents and surgery. The prognosis is influenced by the patient’s age, severity of kyphosis deformity, number of vertebrae involved, lesion site, and patient’s health status, including nutritional status.